THE THE ILLOCUTIVE FORCE IN THE SPEECHES OF THE WINNERS OF THE 2024 IUDC DEBATE IN QATAR: A MULTIMODAL PRAGMATIC PERSPECTIVE: KEKUATAN ILOKUSI DALAM TUTURAN PEMENANG DEBAT IUDC QATAR 2024 PERSPEKTIF PRAGMATIK MULTIMODAL - Salsabila, Alia; Bustomi, Jenal; Ibnu Pamungkas, Muhammad (Jurnal Kata, 2025)
This study aims to analyze the illocutionary force in the speech of the winning team of the Arabic debate at the final round of the 7th International Universities Debating Championship (IUDC) Qatar 2024 from a multimodal pragmatic perspective. This study employs a qualitative approach using descriptive-analytical methods. The data, consisting of audiovisual recordings, were analyzed through three main modes: verbal, aural, and gestural. The results indicate that illocutionary force is dominated by assertive illocution, constructed through the integration of these three modes. Aural elements such as intonation and vocal stress, as well as gestural elements such as body movements and facial expressions, were found to enhance the persuasive power and legitimacy of arguments. This multimodal integration significantly contributes to the speaker’s credibility before the judges. This study confirms that success in competitive debates is highly dependent on the integrated management of multimodal communication in building illocutionary force.